Geomatics approach to assess nesting habitat of green turtles Wadi El Gemal, Red Sea, Egypt - Mostafa A. Soliman; Sameh B. El Kafrawy; Rashad E.M. Said; Samy A. Saber; Frank E. Muller-Karger (Egyptian Journal of Remote Sensing and Space Sciences, 2021)
Long-term wave action, sea level rise, climate change, human activities, pollutants, sea surface temperature SST, are causative factors for deterioration and changes in natural ecosystems. The current study aims to assess environmental deterioration that disturbs turtles and their nesting grounds at Wadi El Gemal National Park (WGNP), using modern remote sensing techniques and ecological investigations. Nesting area mapping and change detection were found to be precise and clear in the current investigation. The true nests recorded from WGNP during the current survey were Wadi El Gemal Delta (3), Torfa (10), Elshiekha Sabieha (2), Hankorab (14), Umm Alabas, Wadi El Gemal Island (1) and Syial Island (1). The concentration of some heavy metals in eggshells were positively correlated with their concentrations in sand (p ≤ 0.01), while heavy metals in nesting sands were negatively correlated with grain size (p < 0.05). On the other hand, the distance from vegetation and SST found to interact with the number of nests. Wadi El Gemal Island declined from 1984 to 1990 at a rate of (0.861 %), from 1990 to 2003 at (2.093 %), and (4.059 %) between 2003 and 2016. According to the shift detection review, Syial Island was reduced in area from 1973 to 1984 (−12,523 m2). Wadi El Gemal shoreline accretion was about (16,777 m2) from 1973 to 1984, while erosion was about (16,777 m2) during the same period (393.754 m2). For the entire period (42 years), the overall shift in accretion area was (362,175 m2), while the erosion area was approximately (724.269 m2).